ANALISIS RESPON SISWA TERHADAP PENGEMBANGAN HYBRID LEARNING BERBASIS MOODLE PADA MATA PELAJARAN IPA DI SMAN 4 KENDARI - Pebrianti, Anggita; Darman , Darman; Fajriani, Alfiah (Program Studi Pendidikan Informatika, Universitas Citra Bangsa, 2024)
The results of this study show that the combination of online learning and project learning is an effective approach in improving the quality of learning. This has important implications for the development of education in the future, where innovative and flexible learning methods are increasingly needed.